Measuring the capacity utilization of China's regional construction industries considering undesirable output. (10th April 2020) - Zhang, Jingxiao; Cai, Wenyi; Li, Hui; Olanipekun, Ayokunle Olubunmi; Skitmore, Martin
Abstract: As most industries in developing countries still follow a relatively rough development model, relying on expansionary investment and paying high environmental costs to promote economic growth, they also face the predicament of excess capacity. Conducting capacity utilization (CU) measurement research is the core of dealing with excess capacity. However, most existing research into capacity utilization is concentrated in the manufacturing, coal, and other industries. The quantitative evaluation of the construction industry capacity utilization is very rare, and the environmental impact factors are neglected. This study aims to develop a capacity utilization measurement index system and use it for the measurement of the construction industry capacity utilization. In doing this, based on the undesirable output perspective, it establishes a capacity utilization measurement index system that considers energy consumption and undesirable output (CO2 ) for the measurement of construction industry capacity utilization. Two data envelopment analysis-based (DEA-based) difference methods (the "no variable-link difference" and the "adding variable-link difference" methods) are used to measure China's construction industry capacity utilization between 2011 and 2017. The findings indicate that using the adding variable-link difference method is more accurate than the no variable-link difference method. It is also shown that the underutilization of capacity in China's construction industry in 2011–2014 is more serious, but it has improved in the past three years. In addition, with the exception of the Jiangsu and Guangxi provinces, there is underutilization of capacity in the construction industry in other provinces and cities in China. This study extends the existing knowledge system of capacity utilization, including the evaluation system, measurement, and assessment of capacity utilization, and management implications. Based on the perspective of undesirable outputs, this study lays a foundation for research into the capacity utilization in various industries by considering environmental factors. This study has practical significance for China and other developing countries to establish a nationwide capacity monitoring system. Highlights: Applying no/adding variable-link difference methods to measure the capacity utilization of the construction industry. 2011–2017 Chinese construction industry panel data was used. Adding variable-link difference proves to be a more appropriate method to measure capacity utilization. Underutilization of capacity in the Chinese construction mainly caused by an unreasonable allocation of variable inputs. There is a significant difference in capacity utilization between regions.